Effect of Simple Electric Circuits Teaching on Conceptual Change in Grade 9 Physics Course - KÜÇÜKÖZER, Hüseyin; KOCAKÜLAH, Sabri (Journal of Turkish Science Education, 2008)
The aim of this study was to examine the effect of teaching designed to consider grade 9 students’ misconceptions about simple electric circuits on conceptual change. Students’misconceptions were determined by using a conceptual understanding test consisting of eight openended questions and semi-structured interview technique. Conceptual understanding test wasapplied as a pre-test at the beginning of the teaching and as a post-test at the end of the teaching while it was applied after six months later as a delayed post-test. Concept of voltage was chosen as the main concept during the teaching that was designed to support conceptual change. Misconceptions brought up in this study were presented in tables with their percentages across threetests and especially the activity concerning the misconception of “consumption of current” was examined to reveal how the ideas of the students changed in details. Mostly, the activities used forconceptual change brought about positive influences on students’ ideas.